The Effect of Feldenkrais Exercise on Reducing Lower Back Pain in Elderly Social Services of Banten Province - Annisa Putri Fahmawati; Junaidi Junaidi; Nadya Dwi Oktafiranda; Ela Yuliana; Sandi Prayudho (Journal Of Sport Education (JOPE), 2024)
This study aims to determine the effect of Feldenkrais Exercise to reduce pain in elderly people suffering from low back pain at the Banten Provincial Social Service Home. The research method used is pre- experimental method with Pre and Post Test with One Group Design. By comparing two evaluation results, namely pre-test and post-test. In this study, the instrument used was Numerical Rating Scales (NRS) which is used to assess pain intensity using numbers 1-10. The population in this study were elderly people at the Banten Provincial Social Service Home totaling 54 people, the sample in this study amounted to 10 people, using purposive sampling technique that met the inclusion criteria. With the data analysis technique in this study using the Wilcoxon Test (paired sample test) which is a non-parametric test. Based on the results of hypothesis testing, it is found that the hypothesis is accepted, namely Feldenkrais exercise has an effect on reducing low back pain in the elderly at the Banten Provincial Social Service Home where the average value of positive rank = 0.00 and negative rank = 5.50, so there is a decrease in low back pain in the elderly. Based on the results of the research that has been described, it can be concluded that there is a decrease in low back pain as evidenced by the data results with a value of 0.004 <0.05, so there is a significant difference. This concludes that Feldenkrais exercise can be used as an exercise program that is easy for the elderly to do in reducing low back pain.